Pendekatan Ilmu Sosial dan Humaniora dalam Studi Islam - Septi, Nurmala; Habibah, Mar'atul; Ash-Saudah, Shofia; Sukti, Surya (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
Islamic studies is a broad and multidimensional academic field, covering various aspects from theology, law, history, to social practice. This paper aims to find out and analyze how the social science approach in Islamic studies and how the humanities approach in Islamic studies. The results of this study can be seen that the social science approach in Islamic studies is a perspective or method that uses concepts, theories, and analysis from social science disciplines such as sociology, anthropology, history, and political science to understand religious phenomena, especially Islam. The humanities approach in Islamic studies is a method that uses disciplines such as history, philosophy, literature, and cultural studies to understand Islam from an intellectual and cultural perspective. Each of these approaches contributes to a deeper understanding of how Islam interacts with different aspects of society, culture and history.